Methylmercury varies more than one order of magnitude in commercial European rice. (1st January 2017) - Brombach, Christoph-Cornelius; Manorut, Parinda; Kolambage-Dona, Piumi P.P.; Ezzeldin, Mohammed Farouk; Chen, Bin; Corns, Warren T.; Feldmann, Jörg; Krupp, Eva M.
Abstract : Graphical abstract: Highlights: MeHg and total Hg were measured in 87 rice and rice products from European markets. 9 baby rice products among 19 samples were validated by two orthogonal methods. MeHg in precooked baby rice shows a higher proportion of MeHg versus total Hg. European rice shows significantly higher variability than rice from other origins. A significant number of rice samples was above 10% of the PTWI. Abstract: Rice is known to accumulate methylmercury (MeHg) in the rice grains. MeHg as a neurotoxin impacts on the human central nervous systems and especially on the developing brain. In this exploratory study, 87 commercial rice products sold in Europe, including nine baby-rice products, were analyzed for total Hg and MeHg content. MeHg concentration in all rice products investigated range from 0.11 to 6.45 μg kg −1 with an average value of 1.91 ± 1.07 μg kg −1 and baby-rice is not significantly different from other rice products. Total Hg ranges from 0.53 to 11.1 μg kg −1 with an average of 3.04 ± 2.07 μg kg −1 . MeHg concentrations in all rice products studied in this work would not exceed the provisional tolerable weekly intake (PTWI). 30% of all commercial market rice products exceeded 10% of the PTWI calculated for toddlers or 13% of products for adults with rice based diet.